War for the peace in Pakistan - Ali, Syed Masroor (2011)
Pakistan because of its geographical location became a front line state in the war against terror since the attack on the World Trade Centre on September 11, 2001. Pakistan decided to align with USA to combat the so-called fundamentalist and Islamic terrorist. During last 5 years about 7000 people were killed and 10,000 were seriously injured. Currently, the biggest threat to the state and citizens is the killing of innocent civilians in suicidal and other attacks.